STUDY OF PRE-DUCTAL AND POST-DUCTAL OXYGEN SATURATION LEVELS IN HEALTHY LATE PRETERMS IN FIRST TEN MINUTES OF LIFE (Journal of Pharmaceutical Negative Results, 2022)
Background: This study is to determine the pre-ductal and post-ductal oxygen saturation levels in healthy late preterm neonates in first ten minutes on life. Method: Healthy late preterm newborns between 34weekes to 37 weeks, who do not require any resuscitation measures were included in the study. Continuous recording was done using pulse oximetry in first ten minutes of life. Result: Out of the 71 babies, 39 (54.9%) were male babies and 32 (45.1%) were female babies, out of which 38 (55%) was delivered via normal vaginal delivery and 32 (45%) was via LSCS. Preductal target oxygen saturation level was achieved faster when compared to postductal oxygen saturation levels. Both preductal and postductal oxygen saturation levels is significantly lower in babies delivered via LSCS. Conclusion: All newborns, especially preterm infants, should be resuscitated using low oxygen concentrations. Additionally neo-natal resuscitation stages be determined based on clinical findings as well as oxygen saturation monitoring. Pulse oximetry screening in all newborns at time of birth helps in detecting various underlying congenital heart diseases and other causes of respiratory distress.